Analysis of Law Enforcement Efforts Against the Perpetrators Online Gambling Causing Violence in The Household (Domestic Violence) (Case Study on Residents of Candipuro District South Lampung Regency) - Prasetyawati, S Endang; Hasan, Zainudin; Pratiwi, Mila Oktavia; Fernando, Avian Chrisna; Salsabila, Nur (CV. Rayyan Dwi Bharata, 2025)
Involvement in online gambling practices in Candipuro District, South Lampung Regency, has had not only economic but also social impacts, particularly in the form of domestic violence (DV). This study aims to analyze the extent of law enforcement efforts against online gambling perpetrators who cause DV, and to identify various inhibiting factors in this process. The study uses a normative and empirical juridical approach, with data collection through library studies and field research. The data used includes primary data from direct interviews and secondary data from legal literature. The results show that although the Electronic Information and Transactions Law (UU ITE) has been used as the legal basis for handling online gambling cases , its implementation still faces serious challenges. Technical obstacles such as the lack of capacity of officers in handling cybercrime, limited digital infrastructure at the police level, and a patriarchal culture that prevents victims of DV from reporting are the main obstacles. Furthermore, the low level of public understanding regarding the legal and social impacts of online gambling also exacerbates the situation. To address this problem, strategic and integrated steps are needed, such as increasing the technical capacity of law enforcement officers, providing digital investigation tools, legal education campaigns for the public, and a cultural approach involving traditional and religious leaders to change norms that are detrimental to victims.